PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK TERPADU BERBASIS PENDEKATAN SAINTIFIK DALAM RANGKA IMPLEMENTASI KURIKULUM SD 2013 PADA SD PILOTING KABUPATEN BULELENG - I Made Ariasa Giri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This research aims to develop a thematic learning tool based integrated scientificapproach to scene at home and travel safety Class II in the framework of implementation ofCurriculum 2013 SD SD Piloting In Buleleng regancy. Learning development at home andtravel safety theme. The study design was used Researsh and Development (R & D) with thedevelopment model be adopted is the 4D model (define, design, develop, and desseminate).These samples included six elementary schools are implementing the curriculum in 2013 in thenumber of practitioners Buleleng District 6 elementary school teacher. The research methodwith descriptive analysis using validity parameters, the quality of the product design lessonplans with teachers' perceptions of the instrument and integrated thematic learning. Theinstrument used is the Lesson Plan Assessment Tool (APRP), Learning ImplementationAssessment Tool (APPP), and instrument teachers insight to an integrated thematic learning.The results showed that: (1) quality RPP generated by test experts and practitioners was verygood, (2) the quality of the lesson plan in a limited test was good (3) the teacher insight forintegrated thematic learning is at a good qualification.